The effect of the second messenger cyclic AMP on scinderin redistribution, F-actin disassembly and catecholamine secretion in bovine adrenal chromaffin cells. - Ramirez-Lavergne, Carmen. (University of Ottawa (Canada), 1994)
Work in our laboratory has demonstrated that stimulation of bovine chromaffin cells with nicotine elicits as a prelude to exocytosis, (a) redistribution of scinderin (Sc), a novel 80 kD Ca$\sp{2+}$-dependent actin filament severing protein and (b) cortical F-actin disassembly. The work presented in this thesis shows that the second messenger, cyclic AMP (cAMP) modulates Sc redistribution, F-actin disassembly and catecholamine (CA) secretion. Here we show that forskolin (F) produces a concentration-related (10 $\mu$M-50$\mu$M) inhibition of Sc redistribution, F-actin disassembly and CA release in response to 10 $\mu$M nicotine. F also induces a concentration-dependent (10 $\mu$M-50 $\mu$M) increase in cAMP levels. Increasing intracellular cAMP with 50 $\mu$M F or incubation with the F analogs 6-acetyl-7-deacetylforskolin or deacetylforskolin (100 $\mu$M) as well as the cAMP membrane permeant analog, 8-Bromo cAMP (2.5mM) for 40 s also inhibits Sc redistribution, F-actin disassembly and CA secretion. The inhibitory effect of F on nicotine-induced Sc redistribution and F-actin disassembly is observed even upon 5 s of incubation while inhibition of CA secretion cannot be detected until 20 s of incubation with F. These effects are accompanied by an increase in cAMP. The discrepancy in timing between inhibition of both Sc redistribution and F-actin disassembly in relation to CA secretion may be explained by the fact that Sc redistribution and F-actin disassembly seem to occur simultaneously and to precede secretion. Although work on cAMP by others has yielded conflicting results, our findings suggest that cAMP may play a role in modulating cytoskeleton dynamics during secretion. This also implies that this second messenger can attenuate the secretory response either by preventing disassembly of F-actin or activation of Sc thus, denying the secretory vesicles access to exocytotic sites. Alternatively, the observed effects may represent a modulation of nicotinic receptor activity by cAMP.
Keywords: Biology, Molecular.